Hambatan dalam pembelajaran digital: tantangan guru dan siswa - Tazkiyah, Azza Bilak Lai (Maliki Interdisciplinary Journal, 2025)
The development of technology in the field of education has encouraged the implementation of digital learning as an interactive and effective approach. However, several challenges arise in the practice of digital learning at MAN 2 Malang Turen, particularly related to the limited availability of projectors, the difficulties faced by senior teachers in adapting to technology, and the misuse of digital devices by students. This study employed a descriptive qualitative approach with data collected through in-depth interviews, direct observations, and documentation. The findings revealed that out of 16 classrooms, only 3 active projectors were available, requiring teachers to take turns using them. This situation affected the effectiveness of the teaching and learning process, reduced the interactivity of lessons, and lowered students’ learning motivation. Moreover, senior teachers faced difficulties in operating digital media due to limited technical skills and a lack of confidence, leading them to prefer traditional lecture methods. On the other hand, students tended to misuse digital devices such as mobile phones during lessons, which disrupted their concentration. These findings highlight the urgency of improving digital facilities in schools, providing continuous and empathetic technology training for teachers, and strengthening students’ digital literacy to support more effective, engaging, and relevant learning in the digital era.